Update in Lung Cancer 2014 - Spira, Avrum (Am J Respir Crit Care Med, 2015)
In the past 2 years, lung cancer research and clinical care have advanced significantly. Advancements in the field have improved outcomes and promise to lead to further reductions in deaths from lung cancer, the leading cause of cancer death worldwide. These advances include identification of new molecular targets for personalized targeted therapy, validation of molecular signatures of lung cancer risk in smokers, progress in lung tumor immunotherapy, and implementation of population-based lung cancer screening with chest computed tomography in the United States. In this review, we highlight recent research in these areas and challenges for the future.